Influence of collagenous material during frozen storage when added to minced cod (Gadus morhua) - Borderías, A. Javier; Martí, M. Angeles; Montero García, Pilar (Zeitschrift fr Lebensmittel-Untersuchung und -Forschung, 1994)
The influence of added purified collagenous material from skin on minced fish during frozen storage is studied with a view to improving the sensory quality of the frozen product. The base material used was minced cod muscle, thawed and fresh, to which collagenous material was added in varying proportions. Following purification, the collagenous material was prepared in four different ways (frozen, pre-solubilized/frozen, freeze-dried and pre-solubilized/freeze-dried) for stabilization before addition to the fish mince. This collagenous material was found to have a positive effect on water-holding ability and to improve the sensory properties of the fish mince during frozen storage. © 1994 Springer-Verlag. Peer Reviewed